John Bartlow Martin : A Voice for the Underdog - Boomhower, Ray E., 1959- (Book collections on Project MUSE., 2015)
During the 1940s and 1950s, one name, John Bartlow Martin, dominated the pages of the "big slicks," the Saturday Evening Post, LIFE, Harper's, Look, and Collier's. A former reporter for the Indianapolis Times, Martin was one of a handful of freelance writers able to survive solely on this writing. Over a career that spanned nearly fifty years, his peers lauded him as "the best living reporter," the "ablest crime reporter in America," and "one of America's premier seekers of fact." His deep and abiding concern for the working class, perhaps a result of his upbringing, set him apart from other reporters. Martin was a key speechwriter and adviser to the presidential campaigns of many prominent Democrats from 1950 into the 1970s, including those of Adlai Stevenson, John F. Kennedy, Lyndon B. Johnson, Robert F. Kennedy, Hubert Humphrey, and George McGovern. He served as U.S. ambassador to the Dominican Republic during the Kennedy administration and earned a small measure of fame when FCC Chairman Newton Minow introduced his description of television as "a vast wasteland" into the nation's vocabulary.